Analisis Strategi Manajemen Digital pada UMKM dengan Upaya Meningkatkan Daya Saing di Pasar Lokal - Moh Afrizal Miradji; Siti Istikoroh; Novi Lailatul Fitri; Citra Devy Arista; Novita Boymau (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Technological advances are closely related to the evolution of the times. The 21st century has seen tremendous digitalization. The number of digital-related activities and activities is increasing in this digital era. Like the rampant online buying and selling that is currently happening in the community. For some organizations, this activity offers many benefits. Because the buying and selling procedure is more effective and realistic. Nowadays, it is possible to search and buy almost anything online without physically meeting the seller. In the modern era, many micro businesses benefit from digitalization, so online buying and selling is not only for corporations or large-scale production. Through digital transformation, digital strategy, and digital capability development, MSMEs, or micro, small, and medium enterprises can now increase their competitiveness in the local market by implementing digital management strategies. While digital tactics can increase customer awareness and loyalty, digital transformation can help MSMEs improve their operational efficacy and efficiency. Through the adoption of digital technology and improving the skills of human resources, MSMEs can also become more competitive through the development of digital capabilities. It is not impossible for MSMEs to grow rapidly and generate significant income with the help of digitalization and a good management plan.